Distribution of proteoglycans during the hair growth cycle in human skin - Westgate, G E; Messenger, A G; Watson, L P; Gibson, W T (Journal of investigative dermatology, 1991)
The involvement of proteoglycans in hair growth has been recognized through the observation of increased hair growth in diseases such as the mucopolysaccharidoses and pre-tibial myxedema, which involve an increase in skin proteoglycan content. In an attempt to understand this, we have examined the distribution of chondroitin 6 sulphate (C6S), unsulphated chondroitin (COS), dermatan sulphate (DS), and heparan sulphate proteoglycans (HSPG) in frozen tissue sections of normal scalp by immunostaining. Results show that during anagen, the thick connective tissue sheath around the follicle strains strongly for C6S, COS, and DS. COS is uniquely associated with this region and is not found beneath the epidermis or infundibular epithelium. HSPG is, however, localized in the basement membrane zone adjacent to the outer root sheath. In addition, all of these proteoglycans are localized in the dermal papilla. In mid-catagen, we observed significant loss of C6S and COS staining from both the dermal papilla and the connective tissue sheath, but no decrease in staining for HSPG. In late catagen, very little staining of C6S and COS was observed. In early anagen, we observed that C6S was again present in the connective tissue sheath and dermal papilla; however, COS staining appeared to be weaker and less closely associated with the follicle. HSPG staining was observed in early anagen in a pattern very similar to that found for other basement membrane components. Results for DS were not obtained for catagen or early anagen. These results provide further evidence that hair growth is associated with the presence of chondroitin proteoglycans in the follicle environment and that the cessation of growth is associated with their removal. Further studies are underway to characterize the relationship between hair growth and proteoglycans.